Avaliação dos sintomas gastroduodenais, integridade da barreira mucosa e inflamação duodenal em pacientes com Covid-19 - Moura, Larissa Gurgel Mota Saraiva (2023)
Brazil was one of the many countries affected by COVID-19, with the Northeast region being one of the most affected. In addition to respiratory symptoms, digestive symptoms are common with SARS-CoV-2 infection. The mechanisms associated with the development of these symptoms are complex and may involve changes in motility, visceral hypersensitivity and impaired duodenal barrier function. The present study aimed to analyze gastroduodenal symptoms during and after COVID-19, correlating them with the severity of the infection, as well as to analyze whether the persistence of symptoms can be related to duodenal barrier integrity dysfunctions or to the inflammatory response. This is a prospective longitudinal cohort study developed with 55 patients hospitalized because of COVID-19. Data collection was carried out from May to July 2021, and the same patients were contacted 6 months after hospital discharge. All patients answered the ROMA III functional dyspepsia and Gastrointestinal Symptom Rating Scale. Of the recovered patients, 25 underwent upper digestive endoscopy with duodenal biopsies to study the epithelial barrier function (transepithelial electrical resistance and permeability of the mucosa to fluorescein) and analyze the concentration of inflammatory cytokines (IL-1 β, IL-8, IL -6 and TNF-α). These results were compared with those of 8 healthy subjects. A high frequency of gastroduodenal symptoms was observed during COVID-19 infection, not correlated with disease severity. On the other hand, when comparing the frequency and intensity of gastroduodenal symptoms during and after COVID-19, there was an increase in the total symptom score, as well as when evaluating gastroduodenal symptoms isolated. Baseline transepithelial electrical resistance showed no statistical difference when comparing with healthy control and post-COVID-19 with or without gastroduodenal symptoms. There was a significant decrease in duodenal patency in post-COVID-19 patients with gastroduodenal symptoms compared to patients without symptoms or normal controls. The concentrations of pro-inflammatory cytokines (IL-1 β, IL-8, IL-6 and TNF-α) did not differ between groups. It is concluded that gastroduodenal symptoms were prevalent during COVID-19, but were not related to the severity of the disease. There was an increase in the intensity and frequency of gastroduodenal symptoms post-COVID-19, unrelated to the loss of mucosal integrity or the increasing of duodenal inflammatory response.